Dampak Brand Image, Harga dan Kualitas Produk Terhadap Keputusan Pembelian Skincare Skintific - Manalu, Dinda Ayu Nisa; Muchsin, Muchsin Muchsin (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2024)
This study aims to analyze the Impact of Brand Image, Price and Product Quality on Skintific Skincare Purchase Decisions (Case Study on FEB Students of Malikussaleh University). The population in this study is students of the Faculty of Economics and Business, Malikussaleh University who use Skintific brand skincare. Sampling in this study used the convenience sampling method and totaled 105 respondents. The data analysis technique in this study is using multiple linear regression analysis. The results of the study show that brand image, price and product quality have a positive and significant effect on purchase decisions. Keywords: Brand image, price, product quality